Spontaneous rupture of splenic artery aneurysm in pregnancy: an autopsy-based case report - Anand, Aditya; Gupta, Mohit; Kumath, Manish; Kumar, Sanjay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Splenic artery aneurysm (SAA) is an infrequent form of vascular disease that has a significant potential for rupture, resulting in life-threatening intraperitoneal hemorrhage commonly during pregnancy. The incidence of splenic artery aneurysms has been estimated between 0.01% and 0.98%. We describe a case of sudden death of a 36 years old full term, primigravida female. During autopsy we found ruptured splenic artery aneurysm about 2.0 cm in diameter near hilum with intraperitoneal hemorrhage. It is important to be alert about the possibility of SAA in pregnant women for its early diagnosis, as the chance of it getting ruptured during pregnancy is high with high maternal and fetal mortality rates.